2020
DOI: 10.5770/cgj.23.399
|View full text |Cite
|
Sign up to set email alerts
|

Mental Health and Cognition in Older Cannabis Users: a Review

Abstract: Background The impact of cannabis use on mental health and cognition in older adults remains unclear. With the recent legalization of cannabis in Canada, physicians will need up-to-date infor­mation about the mental and cognitive effects of cannabis use in this specific population. Method A narrative review was conducted to summarize the literature on mental health and cognitive effects of cannabis use in older adults using Medline (OvidSP). Results A total of 16 studies were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 40 publications
1
11
1
Order By: Relevance
“…Despite these limitations, three reviews have summarized findings on cannabis use and cognition in samples that include older adults. One recent review of cannabis use in older adults (Vacaflor et al, 2020) found that 17.5% of participants across seven studies (three prospective observational studies, one retrospective survey, and three double-blind randomized controlled trials) reported SMC, although study authors concluded that low-dose, short-term medical cannabis use was generally well tolerated in older adults and did not confer significant risk for adverse cognitive outcomes. These findings were similar to a review of recreational and medical cannabis use in middle to older adulthood (Scott et al, 2019) that found modest reductions in cognitive performance associated with higher doses and heavier lifetime use of cannabis, although negative cognitive effects were less evident in older adults using medical cannabis.…”
Section: Introductionmentioning
confidence: 99%
“…Despite these limitations, three reviews have summarized findings on cannabis use and cognition in samples that include older adults. One recent review of cannabis use in older adults (Vacaflor et al, 2020) found that 17.5% of participants across seven studies (three prospective observational studies, one retrospective survey, and three double-blind randomized controlled trials) reported SMC, although study authors concluded that low-dose, short-term medical cannabis use was generally well tolerated in older adults and did not confer significant risk for adverse cognitive outcomes. These findings were similar to a review of recreational and medical cannabis use in middle to older adulthood (Scott et al, 2019) that found modest reductions in cognitive performance associated with higher doses and heavier lifetime use of cannabis, although negative cognitive effects were less evident in older adults using medical cannabis.…”
Section: Introductionmentioning
confidence: 99%
“…32 There is also need for better characterization of the behavioral symptoms that may be most responsive to the effects of cannabinoid drugs, in addition to detailed profiling of compounds, doses, and treatment duration. 33,35 In the present study, we analyzed the available publications that were systematically retrieved from the literature according to the criteria established, using The level of evidence provided by the different studies will be discussed across the topics "efficacy," "safety/ tolerability," and "limitations. "…”
Section: Discussionmentioning
confidence: 99%
“…This apparent effectiveness is not without caveat; although prior studies suggest short-term side effects are minimal,27 abuse and dependence are well-documented. Furthermore, certain populations, specifically pregnant women, children and teenagers, and people with mental illness may be at greater risk of negative consequences from cannabis 37,38. Research suggests cannabis use has been increasing among pregnant women39 and likely among children as well, given its widespread availability.…”
Section: Discussionmentioning
confidence: 99%